Ant Colony Optimization With Look Forward Ant In Solving Assembly Line Balancing Problem - Sulaiman, Mohd Nor Irman; Choo, Yun Huoy; Chong, Kuan Eng (2011)
This work presents an approach based on the ant colony optimization technique to address the assembly line balancing problem. An improved ant colony optimization with look forward ant is proposed to solve the simple assembly line balancing problem of type 1 (SALBP-1). The proposed algorithm introduces an approach to dynamically assign the value of priority rule or heuristic information during the task selection phase by allowing the ant to look forward its direct successors during the consideration in selecting a task to be assigned into a workstation. The proposed algorithm is tested and compared with literature data sets and the result from the proposed algorithm shows competitive performance against them.